DAMPAK REVITALISASI BUDIDAYA UDANG TERHADAP PENDAPATAN DAN RISIKO USAHA PADA USAHATANI TAMBAK UDANG PUTIH - Sigit Suhendra; R. Hanung Ismono; Hurip Santoso (Politeknik Negeri Lampung, 2010)
This research aims to analyze factors that influence production, Income farm business and Effort risk in farm business of white shrimp at PT Aruna Wijaya Sakti. This research is carried out during 2 months at PT AWS, Rawajitu Timur, Tulang Bawang regency. Research method is used randomly sampling where 98 nuclear farmers made sample that consist 30 person farm business the shrimps after revitalization and 68 from nuclear farmers farm business the shrimp not yet revitalization. Observation result data is analyzed by using doubled regression analysis, t-test and Analysis coefisien variance. From research result is got: 1). Factors that influence production in farm business white shrimp at PT Aruna Wijaya Sakti is fry and feed, Where does feed factor give contribution towards higher shrimp production than fry factor. 2). Program revitalization shrimp cultivation affects towards income enhanced farm business white shrimp, Where is income farm business white shrimp before revitalization per cycle in vast pond 0.4 ha as big as Rp 1,312,255, while income farm business white shrimp after revitalization as big as Rp 36,529,940. 3). Program revitalization shrimp cultivation affects towards effort risk depreciation in farm business white shrimp. Keyword: Revitalization, farm business , white shrimp.